The evaluation of orthorexia nervosa tendency in primary health care workers - KULAK, ERCAN; DOĞAN, EMRAH; KARAVUŞ, MELDA; HIDIROĞLU, SEYHAN (My University, 2022)
Purpose: The purpose of the current study was to assess the tendency and frequency of orthorexia nervosa (ON) among primary health care workers. At the same time, it was our special purpose to evaluate its relation with eating attitude disorders and obsessive-compulsive symptoms. Materials and methods: This cross-sectional study was conducted with the participation of primary health care workers in Istanbul, Turkey, in September-October 2016. The total number of 202 primary health care workers were composed of physicians and nurses. We reached 72.2% (n=156) of the research population. Participants completed a questionnaire inquiring about sociodemographic characteristics, and also three scales, namely ORTO11, Eating Attitude Test-40 (EAT-40), and Maudsly Obsessive-Compulsive Inventory (MOCI). Results: The mean ORTO-11 score of the participants was 26.8±4.8. The ORTO-11 score was higher in the physicians (27.8±4.62) than in the nurses (25.8±5.01) (p=0.018). Therefore, physicians tend to have less tendency for ON. There was a low but statistically significant correlation between the scores of ORTO-11 and EAT-40 (rho=- 0.299 and p<0.001) and MOCI (rho=-0.261 and p=0.001). EAT-40 and MOCI (rho=0.192 and p=0.016) scores were found to be statistically significant at low correlation. Conclusions: The tendency of ON, eating attitude disorder and obsessive-compulsive symptoms were found to be higher in nurses as compared to physicians as far as occupational groups were concerned. There can be a relation between ON tendency and eating attitude disorders and obsessivecompulsive symptoms.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); orthorexia nervosa; eating attitude disorders; obsessive-compulsive symptoms; primary health care workers